2017
DOI: 10.1186/s13049-017-0464-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two emergency medical dispatch protocols with respect to accuracy

Abstract: BackgroundEmergency medical dispatching should be as accurate as possible in order to ensure patient safety and optimize the use of ambulance resources. This study aimed to compare the accuracy, measured as priority level, between two Swedish dispatch protocols – the three-graded priority protocol Medical Index and a newly developed prototype, the four-graded priority protocol, RETTS-A.MethodsA simulation study was carried out at the Emergency Medical Communication Centre (EMCC) in Stockholm, Sweden, between O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
2
9
0
1
Order By: Relevance
“…Our findings are in line with two studies that demonstrated a dispatch priority sensitivity of 82.6% [22] and 86% [23]. However, these studies also included patients Table 3 Outcomes per priority subgroup Data are median (IQR) or n (%), unless otherwise stated.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are in line with two studies that demonstrated a dispatch priority sensitivity of 82.6% [22] and 86% [23]. However, these studies also included patients Table 3 Outcomes per priority subgroup Data are median (IQR) or n (%), unless otherwise stated.…”
Section: Discussionsupporting
confidence: 88%
“…Assistant services are not officially recorded by statistics. In order to reduce these non-life-threatening operations in favour of efficient patient management, various solution approaches have been applied in the past; processes of the emergency medical dispatch centre (EMDC) were improved in respect of emergency call handling, which, however, led to an over-prioritization (false positive assignment of a higher priority level) of many patients [ 21 23 ]. In addition, protocols for handling low-priority patients have been successfully implemented, which lead either to the outpatient usage of a nurse or to telephone consultation [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…mining incidents [11], common training for major chemical incidents is to our knowledge very rare in Sweden. Previously, the general performance of Swedish emergency medical dispatch protocols have been evaluated from various perspectives [12,13]. In the neighbouring country of Finland, the preparedness of the emergency medical services for chemical emergencies has been surveyed, finding unsufficient antidote and decontamination capacity [14].…”
Section: Introductionmentioning
confidence: 99%